The manifestations of digital literacy in social media among Indonesian youth - Acintya Ratna Priwati; Avin Fadilla Helmi (HUMANITAS: Indonesian Psychological Journal, 2021)
Digital literacy capability is a must in the era of internet access, especially in the use of social media. All internet users, especially university students, must practice digital literacy. This study aims to found the common forms of university students' digital literacy behavior when using social media. This study uses a mixed-method approach as it consists of data search using a digital literacy scale, an open-ended questionnaire, and interviews with university students in Yogyakarta. The results of this study indicate that respondents with high digital literacy levels conduct a process of evaluating truthful information by checking trusted sources of information directly and discussing their findings with significant others. The likelihood and ability to evaluate information correctly is affected by family background, formal education, and negative hoax impact awareness. The study also found that after respondents perform across (double) checks, they will usually forward the information, also known as doing a repost. This research implies a description of digital literacy behavior carried out by students in Yogyakarta; with this study, digital literacy behavior expects to provide an overview of information technology policymakers.